非传统空间的声音 ：黄明志现象研究 = A voice in unconventional media : study of Namewee phenomenon - 刘依顺 Low, E Soon (2011)
在马来西亚的语境中，马华加入联盟政府后，其势力逐渐被马来巫统霸权所牵制，而反对党则处边缘政治，无法发挥作用。因此华人传统的表达方式无法突破统治霸权的限制。自网际网络的广泛性使用，一个非传统的表达空间应运而生。黄明志通过直述、嘲讽、粗俗、性器官的字眼，制作出多种涉及马来西亚国家、种族及社会课题的音乐视频作品并发布于网络上，引起了国家乃至国际间的瞩目及争议。本文通过对黄明志作品内容、政治人物及公民社会的回应进行分析。政治霸权和言论自由的制衡与妥协初露于黄明志事件中，审视了非传统空间言论自由的伸缩度。黄明志现象挑起了马来西亚华人对新空间言论自由的思考，成为一股逐渐强大的势力及趋向，在未来言论自由的发展中必然将面对许多挑战。Since it joined the coalition government, the Malaysian Chinese Association is subordinate the power of Malays. Meanwhile, the opposition parties are marginalized with limited political influences. Therefore, the traditional ways that Chinese express their own opinions cannot break the shackles of Malay hegemony. As the Internet grows, an unconventional media come into the arena of expressing views. With the help of Internet, Namewee published various video clips on Malaysia, Malays and society issues, with direct, irony, vulgar, or sexual organs expressions, stirring controversy in this country and even among nations. This study analyzes the contents of the Namewee’s work, and also investigates the responses of political figures and commons. The check-and-balance between Malay hegemony and the freedom of speech has begun to take its form in the Namewee phenomenon, which provides us a window to survey the flexibility of unconventional media. Namewee phenomenon leads Malaysian Chinese to reconsider freedom of speech, which is a growing strong power and trend, and will definitely encounter many challenges in the future.